Effect and mechanism of “Danggui–kushen” herb pair on ischemic heart disease - Hui Li (Elsevier, 2022)
Aims: The purpose of this study was to investigate the mechanism and effects of “Danggui–kushen” herb pair (DKHP) better than single drug in ischemic heart disease (IHD). Methods: IHD model was established by left anterior descending branch of coronary artery in rats. Rats were randomized into six groups and oral administration for 7 days: control, model, Danshen dripping pills (DS) (5.103 g/kg), Danggui (DG) (2.7 g/kg), Kushen (KS) (2.7 g/kg) and DKHP (2.7 g/kg). Electrocardiogram (ECG), myocardial infarction and damage assessment, histological inspection analysis, and various biochemical indexes of myocardial tissue were measured to evaluate the myocardial damage and the protective effects of drugs. The inflammatory levels were identified by HE staining and serum cytokine, and the expression of hypoxia-inducible factor 1α (HIF-1α), inhibitor kappa B kinaseβ (IKKβ) and nuclear transcription factor kappa B (NF-κB) were measured by immunohistochemistry. Key findings: The results suggested that: compared with the control group, model group showed significantly myocardial tissue abnormalities, and increased levels of inﬂammatory cytokine. Treatment with drugs inhibited the increase of α-hydroxybutyrate dehydrogenase (α-HBDH), creatine kinase (CK), creatinekinase isoenzyme (CK-MB), interleukin 1 (IL-1) and interleukin 6 (IL-6). The results of immunohistochemical showed that drugs-treatment inhibited the expression of IKKβ and the P-p65, increased the expression of HIF-1α, which demonstrated that the anti-inflammatory effects of DKHP was achieved by suppressing of NF-κB signaling. Conclusion: These observations indicated that DKHP can ameliorate myocardial injury better than single. And these are related to the inhibition of NF-κB and actives HIF-1α signaling.